AI as a Global Equalizer: How NEP 2020 Can Leverage Artificial Intelligence to Bridge Educational Disparities (LTU Journal of Advanced Computing & Engineering, 2026)
This paper examines the potential of the National Education Policy (NEP) 2020 to transform South Asia’s educational landscape by integrating Artificial Intelligence (AI) to address systemic inequities. Despite rising literacy rates, the region faces deep seated structural divides rooted in geography, gender, and socio-economic status that traditional, "one-size-fits-all" teaching models fail to resolve. The study argues that AI can operationalize the core pillars of NEP 2020 such as universal foundational literacy, multilingualism, and inclusive education for Socio-Economic Disadvantaged Groups (SEDGs) through technologies like adaptive learning platforms, Natural Language Processing for mother-tongue instruction, and predictive analytics for early intervention. By proposing a phased implementation roadmap (2025-2030), the authors emphasize a "human-in-the-loop" approach that prioritizes bridging the digital divide and mitigating algorithmic bias, ultimately positioning AI as a scalable tool to democratize quality education and foster social transformation.